Molecular dynamics simulations of biomolecules and metal atoms in carbon nanotube channels - Lim, Melvin Choon Giap (2012)
The usages of the carbon nanotube (CNT) as a delivery system for nanomaterials and as a template for nanowires are exciting topics to be explored. Although many studies involving the flow in carbon tubules have been carried out, the possible usages of CNT channels with junctions for various applications are not well established. This is due to the poor understanding of the flow phenomena of the encapsulated materials in these CNT channels, and also the difficulties involved in the experimental work in this area. The focus of this thesis is thus to present the novel studies of the flow of biomolecules and metal atoms along CNT channels using molecular dynamics (MD) simulations. The Chemistry at HARvard Molecular Mechanics program is used to assist the in-depth studies of the flow of a 3-base oligonucleotide in CNT channels induced by a pressure difference, whereas simulation programs based on MATLAB have been developed for the detailed investigations of copper atoms flowing along CNT channels. A new method of deriving the velocity rescaling is also developed to calculate the flow velocities of copper atoms due to electromigration in MD simulations. According to our new studies, the junction of a (8,8)-(12,12) CNT channel is found to be able to filter a solvated 3-base oligonucleotide from water molecules. The results also show that the narrowing of the CNT junctions not only aids in speeding up the flow velocities, which improve delivery processes, but also causes the oligonucleotide to fold, which reduces the overall length of the delivered oligonucleotide. Apart from that, the new results for the flow of copper atoms along a CNT channel have shown that the CNT junction acts as a buffer area for the reconfiguration of copper atoms to occur. The results also indicate that the right combination of the temperature, bias voltage, CNT junction size and CNT chirality eases the flow of copper atoms along the channel junctions. The spiral flow phenomenon of copper atoms in the downstream of CNT channels is newly found. The degree of rotation in the spiral flow suggests the way a copper mass can be formed in the channel as copper atoms flow downstream. The study also reveals that a CNT channel with a semiconductor-semiconductor junction results in a better hybrid structure of copper atoms and the downstream section of the CNT channel compared to that with a metal-metal junction, in terms of the compactness of copper atoms in the channel.